Information seeking behaviour of the IIUM law faculty members - Kassim, Gava Mugeraa (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1999)
This study investigated th information seeking behaviour of the IIUM law faculty members. The purpose of this study was to identify the information channels used by the law faculty members for meeting their information needs, information sources preferred by them, the methods employed for getting the needed information and their library use patterns. The survey method, using a questionnaire, was employed for data collection. The questionnaire was distributed to 80 law faculty members and 68 filled-in questionnaires were returned with an overall response rate of 85 percent. It was found that respondents used various sources of information to acquire the needed information. Nevertheless, books were ranked as the most important source for teaching, research and publication purposes. Encyclopedias were the least important information source for the law faculty. The respondents preferred to consult their personal collections first for meeting their information needs. The IIUM Library and colleagues were rankeed 2nd and 3rd respectively for this purpose. The most popular method employed by law faculty to get the needed information from the library was "going to the library personally". However, they also used students and support staff for getting information from the IIUM Library. The Online Public Access Catalogue (OPAC) and CD-ROM were the most frequently used IT-based library sources and facilities. Othe IT-based sources and facilities i.e. audio-visual and multimedia collections were less frequently used. It was found that law faculty used various Internet services and facilities. However, e-mail was the most popular Internet facility. File transfer protocol "ftp" and electronic bulletin boards were the least popular. It was also found that law reports were the most adequate library collections followed by statues. CD-ROM databases and audio-visual materials were considered the least adequate. The IIUM Library was perceived as effective in meeting the law faculty information needs. The study made various recommendations for improving access to information by law faculty members. Several areas were also identified for future research on certain related topics.